2014
DOI: 10.1097/ruq.0000000000000057
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Efficacy of Sonosalpingography and Hysterosalpingogram to Test the Tubal Patency in All Women With Primary and Secondary Infertility

Abstract: Sonohysterosalpingography appears to be inexpensive, minimally invasive, quick, of no risk of ionizing radiation, and well-tolerable first-line diagnostic method for determining the tubal status and uterine cavity and can be performed at the time of conventional ultrasound scan in place of HSG and laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…In contrast, in HSG for evaluation of tubal patency, the sensitivity is 91.67% and specificity is 100% and concluded that Sonohysterosalpingography appears to be inexpensive, minimally invasive, quick, of no risk of ionizing radiation, and well-tolerable first-line diagnostic method for determining the tubal status and uterine cavity. 25 In another recent study conducted by Maheux-Lacroixetal S, Sono-HSG and HSG were directly compared with laparoscopy by chromopertubation & found differences between the two techniques were not statistically significant with a P value of 0.4. In our study also, there is significant agreement between the two tests and the diagnostic accuracy of sono-HSG and HSG was comparable with no significant difference in performance of the two tests.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, in HSG for evaluation of tubal patency, the sensitivity is 91.67% and specificity is 100% and concluded that Sonohysterosalpingography appears to be inexpensive, minimally invasive, quick, of no risk of ionizing radiation, and well-tolerable first-line diagnostic method for determining the tubal status and uterine cavity. 25 In another recent study conducted by Maheux-Lacroixetal S, Sono-HSG and HSG were directly compared with laparoscopy by chromopertubation & found differences between the two techniques were not statistically significant with a P value of 0.4. In our study also, there is significant agreement between the two tests and the diagnostic accuracy of sono-HSG and HSG was comparable with no significant difference in performance of the two tests.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, in HSG for evaluation of tubal patency, the sensitivity is 91.67% and specificity is 100%. 13 Geetha V et al found in their study that, HSG detected 8 women with proximal tubal block, 24 women with a block at mid segment and 16 women with Fimbrial block. 14 Seal SL et al did a study in which Hydrosalpinx was detected in 6 women by SSG, in 5 women by HSG and in 8 women by laparoscopy, tuboovarian mass was detected in 4 women by SSG and in 2 women by laparoscopy, endometriosis was seen in 4 women in SSG and in 5 women by laparoscopy, peritubal adhesions was seen only by laparoscopy in 4 women, fibroid uterus was seen in 2 women by SSG and in 4 women by laparoscopy, whereas ovarian cysts and polycystic ovaries were seen in 6women by SSG, in 2 women by HSG and in 8 women by laparoscopy and concluded that pelvic pathologies were better detected by laparoscopy than by SSG and HSG and SSG detected more pelvic pathology than HSG.…”
Section: Discussionmentioning
confidence: 92%
“…Er werden vijf studies geïncludeerd die aan de inclusiecriteria van de HSG-vraag voldeden: twee IPD meta-analyses Broeze, 2011), een meta-analyse (Maheux-Lacroix, 2014), een observationele studie en een cross-sectionele studie (Malik, 2014).…”
Section: Beschrijving Studiesunclassified
“…Hoewel de studie van Maheux-Lacroix et al, 2014, laat zien dat de sensitiviteit en specificiteit van sono-HSG en HSG overeenkomen wordt niet duidelijk wat de diagnostische waarde van sono-HSG is op enkel-of dubbelzijdige of elke vorm van tuba-occlusie. Malik ( Malik et al, 2014) beschrijft niet specifiek de diagnostische waarde van de sono-HSG voor dubbelzijdige tubaocclusie, maar de sensitiviteit en specificiteit hiervoor zijn wel af te leiden uit de tekst. Een voordeel van sono-HSG is dat gelijk de ovaria en het myometrium kunnen worden beoordeeld en dat er geen stralingsbelasting voor de patiënt is.…”
Section: Verhoeve 2011unclassified